Dialogic Interaction and cyber democracy: a study of Twitter accounts of Pakistani politicians - Amna Khurshid; Bakht Rawan (Journal of Peace, Development and Communication, 2023)
Social media use equalizes the power among public and politicians, which promotes cyber democracy. This study explores dialogic interaction between Pakistani politicians and the public by examining Twitter accounts of politicians of major parties i.e., Pakistan Tehreek-e-Insaf (PTI), Pakistan Muslim League (Nawaz) PML (N), and Pakistan People’s Party (PPP) for the year of 2021. It was hypothesized that among dialogic interaction features, it is more likely that conversations of visitors, usefulness of information, and the style of dialogic interaction will be the dominant features as compared to dialogic loop in Twitter accounts of Pakistani politicians. Content analysis was conducted on twitter accounts of Pakistani politicians (two politicians from each party). Total number of tweets during the selected time was 5421 from which 989 tweets were selected for analysis. The result showed that politicians are using usefulness of information followed by a style of dialogic interaction, dialogic loop and conversation of visitors. The results do not support hypothesis as dialogic loop is not least used feature in tweets of Pakistani politicians.